TRANSFORMING LEARNING IN THE DIGITAL ERA: THE IMPACT OF CANVA APPLICATION ON THE QUALITY OF STUDENT LEARNING IN THE FIELD OF ECONOMICS AND ADMINISTRATION - Andini, Fatma Ari; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to analyze whether the Canva application has benefits in the learning process for students of the Economics and Administration study program at Universitas Negeri Jakarta. The method used in this study is a quantitative approach, while data collection uses a questionnaire. The results of this study indicate that learning media with the Canva application has a positive and significant influence on the learning process of students in the Economics and Administration Study Program at Universitas Negeri Jakarta. This is indicated in the t test results with a significance value of 0.001 <0.05 and a calculated t value of 3.665 > t table 2.034. This means that learning media with the Canva application has an effect on improving the student learning process.